Hubungan Tahap Pengobatan dengan Kualitas Hidup Pasien Multidrug-resistant Tuberculosis di RSUD Dr. H. Abdul Moeloek Provinsi Lampung - Muhammad Rifki Pratama; Asep Sukohar; Khairun Nisa Berawi (CV. Jasa Sukses Abadi, 2020)
Tuberculosis (TB) is the number one infectious disease in the world as the most frequent cause of death. TB infects 10 million people each year and becomes the 10th highest cause of death in the world.Multidrug-resistant Tuberculosis (MDR-TB) is a type of TB germ resistance against at least two first-line anti-tuberculosis (OAT) drugs. MDR-TB treatment certainly takes longer than 18 months. This very long treatment can affect the quality of life of MDR-TB patients. This study is to determine the correlation between the treatment phases with the quality of life of patients with Multidrug-resistant Tuberculosis in Dr. H. Abdul Moeloek Hospital Lampung Province. This study used 68 respondents who had been diagnosed with MDR-TB by pulmonary specialists. Primary data was taken using SF-36 questionnaire to measure the quality of life of MDR-TB patients, then secondary data based on the treatment phases using the medical record of the patient who had filled out the questionnaire. The data is processed and analyzed by the program in the computer. Data were tested by chi-square test and the results were obtained from 30 respondents in the initial treatment phases, 22 people (73.3%) quality of life was poor and 8 people had good quality of life (26.7%), while from 38 respondents at the continued treatment phases, as many as 12 people (31.6%) quality of life is bad and 26 people have good quality of life (68.4%). The result of bivariate analysis showed the variable had a correlation with p-value=0,001. There is a correlation between the treatment phases with the quality of life of patients with Multidrug-resistant Tuberculosis in RSUD Dr. H. Abdul Moeloek.